The Anti-apoptotic Role of 3′-Untranslational Region in Response to Angiotensin II via Mcl1 Expression - Lyu, Dayin; Yan, Hong; Chen, Liyang; Zhang, Lingmin; Du, Yanfeng; Ding, Lexi; Lu, Qiulun (Frontiers in Cell and Developmental Biology, 2021)
Myeloid cell leukemia 1 (Mcl1), an abundant protein in the myocardium, plays an essential role in fibrosis and anti-inflammation in cardiomyocytes to preventing heart failure. However, whether Mcl1 3’-untranslated regions (3’-UTR) has the cardio-protecting function remains unclear. Down-regulation of Mcl1 was observed in adult mice heart tissues after Angiotensin II (AngII) treatment. Consistent with in vivo results, the reduction of Mcl1 expression was identified in AngII-treated neonatal cardiomyocytes. Mechanistically, Mcl1 3’-UTR prevented AngII-induced cardiac apoptosis via up-regulation of Mcl1 and an angiogenic factor with a G-patch domain and a forkhead-associated domain 1 (Aggf1), which plays cardiac-protective role. Our work broadens the scope of gene therapy targets and provides a new insight into gene therapy strategies involving mRNAs’ 3’-UTRs application.